Observation of new bone penetration into titanium rods with various thread pitch - Putri, Tansza Setiana; Eddy, Eddy; Rinanti, Astri; Ishikawa, Kunio (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Titanium is a gold standard material in dental implant treatment due to its biocompatibility and excellent mechanical strength. However, titanium has no bioactivity and osteoconductivity. This has led to studies to develop the osteoconductivity by modifying the surface morphology, such as the thread pitch, which affect the implant stability and bone formation around the implant. This study aims to evaluate the effect of various size of gaps (equivalent to thread pitch) on the bone formation in titanium rods implantation. Initially, titanium rods were cut with different blade sizes: 0.2, 0.3, and 0.4 mm. The gaps were equivalent to dental implant thread pitch. Titanium rods were implanted in the rat’s femur and inserted into the bone marrow. After 2 and 4 weeks of implantation, the rats were euthanized and the implanted femur were extracted. The femurs were resin-embedded and cut into 1-mm thickness. The specimens were observed by backscattered SEM. Two weeks after implantation, new bone started to form and penetrated the pitch. In the wider gaps, the bone penetration was found to be particularly high, and vice versa. After 4 weeks, the new bone formation was greater compared to 2 weeks of implantation, and more bone penetration was observed in the wider pitch. This study is an observational research with qualitative reading of the backscattered SEM images. In conclusion, wider pitch could increase osseointegration by providing larger space for bone formation.